2022
DOI: 10.3390/biomedicines10081856
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Learning and Memory and Their Impact on Alzheimer’s Disease

Abstract: Learning and memory formation rely on the precise spatiotemporal regulation of gene expression, such as microRNA (miRNA)-associated silencing, to fine-tune gene expression for the induction and maintenance of synaptic plasticity. Much progress has been made in presenting direct evidence of miRNA regulation in learning and memory. Here, we summarize studies that have manipulated miRNA expression using various approaches in rodents, with changes in cognitive performance. Some of these are involved in well-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 116 publications
1
14
0
1
Order By: Relevance
“…Early studies suggested that the identification and characterization of unique microbial signatures in neuropsychiatric diseases could provide new possibilities in targeted anti- or pro-biotic treatments [ 31 , 32 ]. However, HMP and parallel GI-tract microbiome studies involving multiple human populations and animal models of AD provided evidence indicating that due to wide variation in the microbial and genetic composition of individual GI-tract microbiomes even during healthy aging, it would be difficult to associate the abundance, speciation and/or complexity of any single microbial genus, species or classification with any single human disease [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 45 , 47 , 55 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This is especially relevant to highly complex and heterogeneous neurological syndromes, such as AD, prion disease and other age-related neurodegenerative disorders, against their complex background of familial genetics, patient age, gender, drug history, age of onset and duration, inter-current disease and other critical environmental and lifestyle risk factors [ 61 , 62 , 63 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies suggested that the identification and characterization of unique microbial signatures in neuropsychiatric diseases could provide new possibilities in targeted anti- or pro-biotic treatments [ 31 , 32 ]. However, HMP and parallel GI-tract microbiome studies involving multiple human populations and animal models of AD provided evidence indicating that due to wide variation in the microbial and genetic composition of individual GI-tract microbiomes even during healthy aging, it would be difficult to associate the abundance, speciation and/or complexity of any single microbial genus, species or classification with any single human disease [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 45 , 47 , 55 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This is especially relevant to highly complex and heterogeneous neurological syndromes, such as AD, prion disease and other age-related neurodegenerative disorders, against their complex background of familial genetics, patient age, gender, drug history, age of onset and duration, inter-current disease and other critical environmental and lifestyle risk factors [ 61 , 62 , 63 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…While commensal GI-tract microbes are beneficial and essential to human health, the enterotoxigenic forms of these same microorganisms have considerable potential to secrete highly neurotoxic biopolymers, including multiple varieties of Gram-negative bacterial-derived glycolipids such as LPSs, which are extremely potent inducers of pro-inflammatory and altered innate-immune and immunological signaling in infection, aging and diseases from AD to cancer [ 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. One major characterized pathogenic role of LPSs appears to be the stimulation of cytokine-, chemokine- and/or ROS-mediated pathological signaling programs that drive the induction of pro-inflammatory transcription factor NF-kB (p50/p65), which subsequently promotes the transcriptional up-regulation of NF-kB-sensitive microRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vast evidence shows that miRNA expression patterns are regulated by neuronal activity 68,69,71,73,123,130–137 …”
Section: Activity‐dependent Regulation Of Mirna Expressionmentioning
confidence: 99%
“…Different technical approaches have been used to look for neurodegeneration-related specific blood biomarkers, such as those of proteomics [ 11 , 12 ] or miRNomics [ 13 , 14 ] or metabolomics [ 15 , 16 ], attempting to detect specific brain molecules —amyloid-beta (A ), tau and glial fibrillary acidic protein neurofilaments light chains [ 17 , 18 ]. On the other hand, fewer studies have been performed to assay non-specific blood analytes in patients with neurodegenerative illnesses [ 19 , 20 ], and more specifically AD [ 11 , 21 , 22 ] to find out novel interesting and useful correlations to brain biomarkers.…”
Section: Introductionmentioning
confidence: 99%